Impact of Changes in Criminal-Legal Practices During the COVID-19 Pandemic on the HIV Risk Behaviors of Women Who Use Drugs: Protocol for a Multimethods Qualitative Study - Smoyer, Amy B. (JMIR Research Protocols, 2024)
Background: HIV risk behavior in women who use drugs is related to myriad psychosocial issues, including incarceration. The experience of incarceration elevates women’s HIV risk by disrupting social networks, housing, employment, and access to health care. During the COVID-19 pandemic, changes in criminal-legal practices resulted in decreased incarceration, especially among women. These changes may have largely altered HIV risk among women who use drugs, depending on their access to care in the community. Objective: This study seeks to build knowledge about the impact of shifts in criminal-legal practices during the COVID-19 pandemic on HIV risk behaviors of justice-involved women who use drugs. Methods: Qualitative methods are used to gather and analyze women’s narratives about their life experiences before and during the COVID-19 pandemic, with a focus on individual and structural determinants of HIV risk behaviors. Thirty formerly incarcerated women with a history of substance use are being recruited through collaboration with community partners. Each participant completes a sociodemographic survey and two interviews. The first interview uses a life history instrument that invites participants to reflect on key turning points in their lives. The second interview uses a calendar approach to gather information about participants’ lives during the first year of the COVID-19 pandemic (March 2020-March 2021). The interviews (1 hour each) are audio-recorded and transcribed for analysis. Rapid Qualitative Inquiry and thematic analysis are being used to manage, organize, and interpret the data. The study team will collaborate with a subset of participants to develop digital stories about their COVID-19 experiences, a process that allows for member-checking and triangulation. Findings will be disseminated to program and policy makers in academic venues, community settings, and social service agencies. Results: To date, 10 women’s data have been collected. In total, two themes have been identified in this preliminary data: (1)the chaos and instability of participants’ lives increased during the COVID-19 pandemic: participants reported a wide range of psychosocial and health problems and limited engagement with social service systems. Interaction with criminal-legal systems was rife with uncertainty; participants described living in a state of limbo, which was extremely stressful. (2) When asked to describe a “turning point” in their lives, many participants attributed their substance use to the traumatic loss of a child due to death, incarceration, or termination of parental rights. During the COVID-19 pandemic, participants’ struggles to cope with these unresolved experiences of grief and loss were intensified by the widespread death and dying of the pandemic. Conclusions: Preliminary findings suggest that HIV risk factors increased for participants during the COVID-19 pandemic and invite further investment in community-based harm reduction programs, especially housing, that support women who use drugs. Interventions that address experiences of maternal grief and loss may reduce women’s substance use. Trial Registration:
Company: JMIR Research Protocols Distributor: JMIR Research Protocols Institution: JMIR Research Protocols Label: JMIR Research Protocols
Keywords: dept.swk; peer-reviewed

Bridging the gap between spirituality and mental health: the need for trauma-informed ministries within Latino communities - Hernandez, V. (Journal of Religion and Spirituality in Social Work, 2024)
The impact of trauma on mental health has led to the increased development of trauma-informed organizations. Little is known, however, about the benefits of using a trauma-informed care perspective within a faith-based setting, particularly among Latino communities. This article reviews the literature and identifies gaps suggesting the problem of a lack of mental health and trauma-informed awareness among places of worship. The need for developing trauma-informed ministries within places of worship is recommended to assist in promoting the psychological, emotional, and spiritual well-being of congregants and community members within faith-based settings. © 2024 Taylor & Francis.
Keywords: Latino; Mental illness; dept.swk; ministry; peer-reviewed; training; trauma-informed

Promoting food justice and the right to adequate food in social work education - Hall-Faul, M.; D’Angelo, K.A.; Libal, K. (Journal of Human Rights and Social Work, 2024)
Food justice is centered on the principle that food is a basic human right. Despite a mandate to include human rights and social justice content in the social work curriculum, food insecurity and food justice receive scant attention in social work academia. Food insecurity affects a substantial portion of the population, with a disproportionate impact on women and Black, Latinx, and Native American communities. A human rights-based approach to food requires more than access to food; it demands that food also be available, adequate, and culturally acceptable. A right to food framework also calls on policymakers to immediately address disparities in food security, which are prevalent in the USA due to historical and ongoing systemic racism. This paper provides a conceptual understanding of food justice and its historical connections to social work, outlines the requirements of a right to food, and concludes by offering strategies to integrate food justice into the micro, mezzo, and macro social work curriculum. © 2024, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Food insecurity; Food justice; Human rights; Hunger; Right to food; Social work; Social work education; dept.swk; peer-reviewed